Carbonic fluid inclusions in ultrahigh-temperature metamorphic rocks from Tonagh Island in the Archean Napier Complex, East Antarctica: A preliminary report - Tsunogae, Toshiaki; Santosh, M.; Osanai, Yasuhito; Owada, Masaaki; Toyoshima, Tsuyoshi; Hokada, Tomokazu; Crowe, Warwick A.; Miyano, Takashi (National Institute of Polar Research, 2001)
P(論文) We report here the occurrence of high density CO_2-rich fluid inclusions in ultrahigh-temperature metamorphic rocks from Tonagh Island of the Archean Napier Complex, East Antarctica. A study on the different lithological units from Tonagh Island (garnet gneiss, sapphirine granulite, garnet-orthopyroxene gneiss, and magnetite-quartz gneiss) shows the common presence of carbonic fluid inclusions entrapped within various minerals. The melting temperatures of fluids in the first three rock types lie in the range of -56.3 to -57.2℃, close to the triple point for pure CO_2 (-56.6℃). Fluid inclusions in magnetite-quartz gneiss show slight depression in their melting temperatures (-56.7～-57.8℃) suggesting traces of additional fluid species such as CH_4 and/or N_2 in the dominantly CO_2-rich fluid. Homogenization of pure CO_2 inclusions in the garnet gneiss, sapphirine granulite, and garnet-orthopyroxene gneiss occurs into the liquid phase at temperatures in the range of -34.9～+4.2℃. This translates into high CO2 densities in the range of 0.9-1.1 g・cm^<-3>. The estimated CO_2 isochore intersects the counterclockwise P-T trajectory of Tonagh Island at around 6-9 kbar at 1100℃, which corresponds to the peak metamorphic conditions of Tonagh Island derived from mineral phase equilibria. We therefore infer that CO_2 was the dominant fluid species present during the ultrahigh-temperature metamorphism in Tonagh Island. The stability of anhydrous minerals such as orthopyroxene in the study area might have been effected by the lowering of H_2O-activity due to the presence of CO_2 at peak metamorphic conditions (>1100℃). departmental bulletin paper